RETRACTED: The role of motivation for self-education in the training of public catering workers - Petržílka Slavibor; Nianko Viktoriia; Poltorak Anastasiya S.; Pet'ko Lyudmila; Ridel T.M. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001